A reconceptualization of filial obligations: case study of Singapore - Ng, Michelle Ee Xiang (Nanyang Technological University, 2023)
Within Singapore, the issue of filial obligations is becoming prominent and contested. This is due to the clambering issue of parental abuse and neglect, as well as the increasingly demanding care burden experienced by the younger Singaporeans towards their elderly parents. As such, this evokes questions about the circumstances under which grown children have an obligation to care for their elderly parents and what happens if they are unable to fully provide for the needs of their elderly parents.